Interactions of TTV with BKV, CMV, EBV, and HHV-6A and their impact on post-transplant graft function in kidney transplant recipients - Rosiewicz, Kamil S.; Blazquez-Navarro, Arturo; Kaliszczyk, Sviatlana; Bauer, Chris; Or-Guil, Michal; Viebahn, Richard; Zgoura, Panagiota; Reinke, Petra; Roch, Toralf; Hugo, Christian; Westhoff, Timm; Thieme, Constantin; et al. (Frontiers in Transplantation, 2024)
Background Mono and combined reactivation of latent viruses occurs frequently under immunosuppressive therapy in kidney transplant patients. Recently, monitoring torque teno virus (TTV) reactivation came more into focus as a potential biomarker for immune status. The surrogate characteristics of TTV reactivation on acute rejection, and the combined reactivation with other latent viruses such as cytomegalovirus (CMV), human BK virus (BKV), Epstein–Barr virus (EBV), and human herpes virus-6A (HHV-6A) on allograft function, are unknown so far. Methods Blood samples from 93 kidney transplant recipients obtained during the first post-transplant year were analyzed for TTV/BKV/CMV/EBV/HHV-6A load. Clinical characteristics, including graft function [glomerular filtration rate (GFR)], were collected in parallel. Results TTV had the highest prevalence and viral loads at 100% and a mean of 5.72 copies/ml (cp/ml) (log10). We found 28.0%, 26.9%, 7.5%, and 51.6% of simultaneous reactivation of TTV with BKV, CMV, EBV, and HHV-6, respectively. These combined reactivations were not associated with a significantly reduced estimated GFR at month 12. Of interest, patients with lower TTV loads <5.0 cp/ml (log10) demonstrated not only a higher incidence of acute rejection, but also an unexpected significantly earlier occurrence and higher incidence of BKV and HHV-6A reactivation. Correlations between TTV loads, other latent viruses, and immunosuppressive medication were only significant from 6 months after transplant. Conclusion We were able to observe and support previously introduced TTV load thresholds predicting kidney allograft rejection. However, due to a possible delayed relation between immunosuppressive medication and TTV viral load adaptation, the right time points to start using TTV as a biomarker might need to be further clarified by other and better designed studies.